Application of Na2SO4·10H2O thermal storage in air-conditioning cooling water system. (May 2015) - Feng, G.; Xu, X.; Li, G.; Li, H.; Huang, K.
<x content-type="archive" xml:space="preserve">Abstract</x> The present paper aims at establishing a phase-change thermal storage air-conditioning cooling water system heat transfer model. The impact factors of phase change materials in the regenerative process were researched by numerical simulation. The amount of phase change materials was determined. Heat storage capacity of the air-conditioning cooling water system after adding phase change materials was predicted. With an increase in Na2SO4·10H2O phase-change thermal storage unit number from 104 to 614, heat storage capacity increases. Heat storage capacity can improve by 30% compared with original heat storage capacity. Analogue values are within the range of ±3–±5% error to experiment results at any time after adding phase change thermal storage units. The maximum result error of simulation results compared to the same conditions experimental results is 12·91%.